2011
DOI: 10.1186/1742-4690-8-7
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between HIV Entry and Transportin-SR2 Dependency

Abstract: BackgroundTransportin-SR2 (TRN-SR2, TNPO3, transportin 3) was previously identified as an interaction partner of human immunodeficiency virus type 1 (HIV-1) integrase and functions as a nuclear import factor of HIV-1. A possible role of capsid in transportin-SR2-mediated nuclear import was recently suggested by the findings that a chimeric HIV virus, carrying the murine leukemia virus (MLV) capsid and matrix proteins, displayed a transportin-SR2 independent phenotype, and that the HIV-1 N74D capsid mutant prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 76 publications
5
74
0
Order By: Relevance
“…These studies, in which CA was artificially expressed as a discrete protein, do not, of course, exclude that core-associated CA derived from Gag cleavage during particle budding has important nuclear import functions in the postentry virion. Although the present work focused on the trafficking of de novo-expressed Gag, which is relevant to the assembly side of the life cycle, there is evidence that FIV and HIV-1 negotiate early events differently in some respects, including the use of nuclear entry pathways (32,34,54). Further comparative investigations of the roles of FIV versus HIV-1 Gag-derived virion structural proteins in preintegration trafficking steps may be informative.…”
Section: Discussionmentioning
confidence: 99%
“…These studies, in which CA was artificially expressed as a discrete protein, do not, of course, exclude that core-associated CA derived from Gag cleavage during particle budding has important nuclear import functions in the postentry virion. Although the present work focused on the trafficking of de novo-expressed Gag, which is relevant to the assembly side of the life cycle, there is evidence that FIV and HIV-1 negotiate early events differently in some respects, including the use of nuclear entry pathways (32,34,54). Further comparative investigations of the roles of FIV versus HIV-1 Gag-derived virion structural proteins in preintegration trafficking steps may be informative.…”
Section: Discussionmentioning
confidence: 99%
“…S6A). (P ut vs. 100nM AZT = 9.555e-05, P ut vs. 1uM = 4.485e-07, P ut vs. 10uM = 4.384e-08, P ut vs. 2uM nev = 0.0003, P ut vs. 10uM nev = 8.572e-13, P ut vs. 100nM ral = 3.466e-11, P ut vs. 500nM ral < 2.2e-16, P ut vs. 1uM ral < 2.2e-16, P ut vs. 100nM CX = 0.0004, P ut vs. 1uM CX = 3.046e-13, P ut vs. 10uM CX = 6.122e-10, KS test Transportin-SR2 (TRN-SR2, TNPO3) is a cellular import factor of SR-rich proteins that is involved in HIV-1 entry in the nuclei of infected cells (24)(25)(26)(27)(28)(29)(30)(31). In fact, after TRN-SR2 knockdown HIV-1 nuclear entry is inhibited and, consequently, the amount of integrated DNA is reduced.…”
Section: Resultsmentioning
confidence: 99%
“…For example, it has been shown that both HIV-1 and MLV INs interact with TNPO3 with similar affinities (19,20). Moreover, a chimeric virus where HIV-1 CA was replaced with its MLV counterpart lost sensitivity to TNPO3, thus highlighting the importance of CA in nuclear import (19).…”
mentioning
confidence: 99%